Fault Kinematics of the 2022 Delingha Mw 5.6 and Mw 5.7 Earthquakes Revealed by InSAR Observations - Wang, Xuening; Wu, Donglin; Liu, Lian; Li, Chenglong; Bai, Yongliang; Huang, Xing (Remote sensing (Basel, Switzerland), 2024)
Between January and April 2022, three moderate earthquakes (Mw 5.6 on 23 January, Mw 5.7 on 25 March, and Mw 5.1 on 15 April) struck the Hala Lake area of Delingha, Qinghai, China. Their seismogenic faults are poorly mapped, resulting in an unclear understanding of their kinematics and regional seismotectonics. In this study, we employed Interferometric Synthetic Aperture Radar (InSAR) observations to reconstruct the coseismic deformation fields of the Mw 5.6 and 5.7 events. We then utilized a Bayesian inversion algorithm to delineate the fault geometries of the two events, and further resolved their coseismic fault slip. Our results reveal that these earthquakes ruptured different fault planes: the fault plane of the Mw 5.6 event dips westward at an angle of 60°, while the Mw 5.7 event ruptured as a nearly vertical fault with a dipping angle of 89°. The finite-fault slip inversions further demonstrate that the coseismic rupture of the Mw 5.6 event was predominantly concentrated between depths of 2 km and 7 km, with a maximum slip of 0.18 m; in contrast, the Mw 5.7 event was mainly concentrated between depths of 2 km and 9 km, with a maximum slip of 0.4 m. We calculated the coseismic Coulomb failure stress change (ΔCFS) induced by these two earthquakes. Integrating the analysis of ΔCFS and the spatial distribution of aftershocks, we argue that the sequence earthquakes were triggered by the proceeding earthquakes.